Amorphous indium gallium zinc oxide thin film transistor and memory device for future device applications - Liu, Pan (2015)
Amorphous Indium Gallium Zinc Oxide (IGZO) is an important material which can be used in transparent thin film transistors (TFTs) due to its high field effect mobility for the next generation flat panel displays. Evolution of electrical properties and TFT characteristics of amorphous IGZO thin films synthesized with radio-frequency (RF) sputtering technique with O2 plasma immersion has been studied. The a-IGZO thin film with O2 plasma immersion can greatly enhance the Hall mobility while largely reduce the electron concentration. The influence of post-deposition O2 plasma immersion has been studied. The electrical properties and the transistor performance can be attributed to the repair in the oxygen-related defects of the IGZO thin films. The threshold voltage (Vth) is an important parameter in TFTs performance which is determined by the electron concentration in the transistor channel layer; however it is not easy to control the Vth as the oxygen vacancies which are related to the electron concentration can be easily generated during the fabrication process. An exposure of the back channel of an IGZO TFT to ultraviolet (UV) activated oxygen can effectively shift the Vth of the TFT. There is a linearly relation between the Vth and the exposure time while the on-state current greatly increase with the exposure time. Other TFT parameters such as the field-effect mobility and sub-threshold swing are not significantly affected by the exposure. An exposure to UV-activated oxygen is a simple way to control the Vth, and the TFT can be easily changed from the enhancement mode to the deletion mode with this technique. The effect of the exposure on the Vth is attributed to the increase in the electron concentration of the channel layer as a result of the creation of oxygen vacancies by exposure. Beside UV-activated oxygen exposure treatment, UV light is commonly used in the cleaning process to remove the particles and impurities on the thin film in the TFT fabrication. An UV exposure can cause a shift in the threshold voltage of IGZO TFT, which poses a problem to normal device operation. The effect of short-duration UV exposure on the Vth of amorphous IGZO TFTs and its recovery characteristics are investigated. The illuminated devices showed a slow recovery in threshold voltage without external bias. However, an instant recovery can be achieved by the application of positive gate pulses, which is due to the elimination of the positive trapped charges as a result of the presence of a large amount of field-induced electrons in the interface region. In the last chapter, the memory devices (e.g. non-volatile memory (NVM) and write once read many times memory devices (WORM)) based on O2 plasma-treated IGZO thin films has been demonstrated. The WORM device has a normally-OFF state with a very high resistance as a result of the O2 plasma treatment on the IGZO thin films. The device could be switched to an ON state with a low resistance by applying a voltage pulse. The WORM device has good data-retention and reading-endurance capabilities.